Assessment of the reliability of operated sections of highways - Yuri V. Burtyl; Denis V. Kapski; Nadezhda A. Filippova; Alexander A. Neretin (International Journal of Advanced Studies, 2025)
Background. The main objective of this study is to develop a methodology for checking the actual reliability of road surfaces based on the dynamics of changes in pavement smoothness, estimated vehicle speed, and estimated service life. The study introduces proprietary quantitative criteria, such as the road structure operational reliability coefficient and the road surface service life coefficient. The study is related to observing changes in road surface smoothness and its impact on performance characteristics. Assessing the wear and tear that occurs during operation is especially important for determining repair periods and the required amount of work. The article provides examples of smoothness measurements on road sections with varying traffic intensities, which allows us to draw a conclusion about the different rates of pavement condition deterioration and identify areas that are most susceptible to deformation.